Analyzing Chinese Customers’ Switching Intention of Smartphone Brands: Integrating the Push-Pull-Mooring Framework - Jin Guo; Shan Shan; Yu Wang; Yousaf Ali Khan (Discrete Dynamics in Nature and Society)
With increasing technology advancement, online shopping, and growth of affordable segment, smartphone users’ switching behavior is becoming a concern for smartphone companies. To fill the research gap that persists in relation to the switching behavior of smartphone users from a multidimensional view, this study integrates the push-pull-mooring model to investigate and classify factors that affect the switching behavior of smartphone users. To test the hypotheses in relation to different predictors, data were collected from a survey of 246 users of the top ten smartphone brands in China and analyzed using structural model equation through regression analyses. The results revealed that the pull, push, and mooring factors have a significant impact on the switching behavior of smartphone users. While the pull effects have a stronger impact than push effects, the mooring factors were found to have a significant and strongest effect on smartphone users’ switching behavior. In particular, subjective norm showed the greatest impact on switching behavior, product quality and obsolete features showed significant and weak impact while brand image, switching cost, and poor customer service did not show any significant impact. These findings provide useful implications and insights for smartphone brands to develop competitive strategies for customer relationship management.